Removal of Phenols from Synthetic Wastewater by Horseradish Peroxidase (HRP) - Nurul Zakiah Md Salleh,; Siti Amira Othman, (Journal of Science and Technology, 2024)
Plant peroxidase has a solid potential to remove phenol from wastewater. However, large-scale use of these enzymes for phenol removal requires a source of cheap, abundant, and easily accessible peroxidase-containing material. In this study, the horseradish peroxidase (HRP) removes the phenolic compound from the phenolic environment. The enzymatic method was used to show a reduction of toxicity between the treated and untreated phenolic solution. The HRP, with the addition of hydrogen peroxide (H2O2), reacted with the phenolic compound and produced a treated solution containing about 20% of phenol compared to the initial acidic solution. The concentration of the treated solution was then determined using UV-Vis and FTIR spectroscopy. The effects of treating the acidic solution with HRP enzyme and H2O2 were studied. The HRP enzyme decreases the amount of phenol present in an acidic solution by 80 %. The most effective concentrations for treating the acidic solution were HRP at 1.0 M and 1.0 M of H2O2 at neutral pH.